Proportion of cervical excision for cervical intraepithelial neoplasia as a predictor of pregnancy outcomes. Issue 2 (February 2015) - Kyrgiou, Maria; Valasoulis, George; Stasinou, Sofia-Melina; Founta, Christina; Athanasiou, Antonios; Bennett, Phillip; Paraskevadis, Evangelos
Abstract: Objective: To assess how the proportion of the cervical volume/length removed during treatment for cervical intraepithelial neoplasia (CIN) varies and whether this correlates to the pregnancy duration at delivery. Methods: The present prospective observational study included 142 women undergoing CIN treatment at a university hospital during 2009–2013. The pretreatment and post-treatment cervical dimensions and cone size were measured with magnetic resonance imaging, three-dimensional transvaginal ultrasonography, or two-dimensional transvaginal ultrasonography, and the correlation between pregnancy outcomes and the relative proportion of the cervix excised was assessed. Results: Pretreatment cervical volumes and cone volumes varied substantially (range 11–40 cm 3 and 0.6–8 cm 3, respectively). The proportion of the volume excised ranged from 2.2% to 39.4%. Sixteen (11%) women conceived following treatment; 12 had a live birth (seven at term, three preterm). The pregnancy duration at delivery was significantly correlated with the proportion of the cervical volume ( r = –0.9; P < 0.001) and length ( r = –0.7; P = 0.01) excised and the cone volume ( r = –0.6; P = 0.04). Conclusion: The pretreatment cervical dimensions and the proportions of the volume/length excised vary substantially, and the latter correlates with the pregnancy duration. Assessment of the proportion excised might help to stratify women at risk who need intensive surveillance when pregnant.